Inovasi Ramah Lingkungan: Sosialisasi Sampah Plastik Menjadi Solusi Inovatif Untuk Pengelolaan Sampah - Firra Rosariawari; Himmatul Aliyah Rosydi; Arini Sayyidah Achmad; Bagas Chrisma Pratama; Safitri Wahyu Pratiwi; Muhammad Ijlal Rafi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Plastic waste is one of the serious environmental problems in Indonesia. Plastic waste not only pollutes the environment, but also has a negative impact on human and animal health. One way to overcome this problem is by utilizing plastic waste into trash bins that can be reused. The purpose of this study is to conduct socialization on the utilization of plastic waste into trash bins to the community in one of the villages in Gresik Regency. This socialization was carried out with students as a form of community service. The method used in this socialization was lecture, discussion, and practice. The results of this socialization showed that the village community had a high interest and enthusiasm for utilizing plastic waste into trash bins. They also felt helped and inspired by this activity. This socialization ran smoothly and received a positive response from the community. This study contributes to the development of science, technology, and environment, as well as improving the skills and social awareness of students.